Innovation of Anti-Bullying Education Model in Islamic Boarding Schools: A Systematic Literature Review - Abdurrohim, Abdurrohim; Rusdiyah, Evi Fatimatur; Abu Bakar, M. Yunus (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research investigates the development of anti-bullying education models in Islamic boarding schools between 2019 and 2024, with a focus on the effectiveness of prevention and intervention strategies. The method used is Systematic Literature Review (SLR), which involves article inclusion and exclusion criteria as well as data extraction and synthesis processes from two main databases, namely Google Scholar and ERIC, through the Publish or Perish version 8 application. A total of 146 articles were identified, but after selection process, only 25 articles met the inclusion criteria, while publications in the form of books and seminar proceedings were excluded due to the tendency for peer-review to be less stringent. The research results show that the two main models, namely early prevention and intervention against perpetrators and victims of bullying, have developed significantly. While both models are important, a humanist educational approach to prevention has stronger potential to reduce bullying incidents. In addition, a comprehensive holistic approach was found which includes humanist, sociological, participatory and psychotherapeutic educational aspects through dhikr. These findings provide practical insights for stakeholders to improve anti-bullying curricula and develop intervention strategies that are more sensitive to the cultural and religious context in Islamic boarding schools.